A study of certain members of the South African xylariaceae, with reference to the use of cultural characters in classification - Martin, Philip Michael Dunlop (Rhodes University, Faculty of Science, Botany Department, 1961)
[Summary] Sixty-three species, drawn from the genera Rosellinia Hypoxylon, Nummularia, Daldinia, Penzigia and Xylaria, are studied in order to determine whether any correlation exists between various characters of the perfect stage and characters connected with the mycelium in artificial culture that might be used to supplement the existing classification of the Xylariaceae. An examination is made of the morphological and anatomical characters of several stromal types and a statistical method of evaluating differences in ascospore dimension between samples of closely related species is described. Cultural work shows that :- a) Each species group, based primarily on similarity of stromal form, has a characteristic set of cultural characters. b) Members within a Species group can usually be distinguished clearly in culture. The use of cultural characters as an additional criterion in classification is therefore recommended.
Keywords: Xylariaceae -- South Africa; Hypoxylon; Fungi -- South Africa -- Morphology; Fungi -- South Africa -- Anatomy; Fungi -- Classification; Mycelium